Role of Reticulated Platelets in Cardiovascular Disease - Bongiovanni, Dario; Han, Jiaying; Klug, Melissa; Kirmes, Kilian; Viggiani, Giacomo; Von Scheidt, Moritz; Schreiner, Nina; Condorelli, Gianluigi; Laugwitz, Karl-Ludwig; Bernlochner, Isabell (Arteriosclerosis, Thrombosis, and Vascular Biology, 2022)
Human platelets differ considerably with regard to their size, RNA content and thrombogenicity. Reticulated platelets (RPs) are young, hyper-reactive platelets that are newly released from the bone marrow. They are larger and contain more RNA compared to older platelets. In comparison to more mature platelets, they exhibit a significantly higher thrombogenicity and are known to be elevated in patients with an increased platelet turnover such as, diabetics and after acute myocardial infarction. Several studies have shown that RPs correlate with an insufficient antiplatelet response to aspirin and specific P2Y12receptor inhibitors. In addition, RPs are promising novel biomarkers for the prediction of adverse cardiovascular events in cardiovascular disease. However, the reason for RPs intrinsic hyper-reactivity and their association with ischemic events is not completely understood and the biology of RPs is still under investigation. We here present a structured review of preclinical and clinical findings concerning the role of RPs in cardiovascular disease.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aspirin; biology; biomarker; myocardial infarction; reticulated platelets